Monitoring the impact of COVID-19 in Myanmar: Agricultural input retailers - Synopsis of results from five survey rounds through late July 2020 - Goeb, Joseph; Synt, Nang Lun Kham; Zu, A Myint; Boughton, Duncan; Maredia, Mywish K. (International Food Policy Research Institute, 2020)
Agricultural input retailers play a key role in Myanmar’s agri-food system by supplying farmers with fertilizer, seed, pesticides, and other inputs necessary for successful harvests. Because farm-level input use is an important driver of yields for all major food crops, shocks from the COVID-19 crisis to the input retail sector have major implications for rural household welfare as well as food security. In this policy note, we present results and analysis on the effects of the COVID-19 crisis on agricultural input retailers from a five-round telephone panel survey of between 150 and 200 retailers in Shan, Kachin, Bago, Ayeyarwady, Sagaing, and Mandalay that was implemented every two weeks from mid-May to late July 2020. 1 The objective of this survey was to provide data and insights to the Ministry of Agriculture, Livestock, and Irrigation (MOALI) and agricultural sector stakeholders so that they better understand the nature of COVID-19 related shocks to Myanmar’s agricultural input retailers. Previous policy notes2 mostly focused on the survey rounds individually, tracking the effects of the COVID-19 crisis on agricultural input retailers as they were happening. In this note, we take a more comprehensive approach by looking back over all five survey rounds to understand how the effects of the COVID-19 crisis evolved over time. In particular, this note presents results from May 2020 through July 2020 across the five survey rounds on (i) disruptions caused by the COVID-19 crisis, (ii) responses to these disruptions, (iii) sales of fertilizer, maize seed, vegetable seed, and pesticides, and (iv) input retailers’ employees and hired labor.